GAMBARAN KADAR GLUKOSA DARAH SEWAKTU PADA MAHASISWA TINGKAT AKHIR PRODI DIII ANALIS KESEHATAN DI UNIVERSITAS ABDURRAB - Rosa Devitria; Mega Elfia; Nissa Aulia (Ensiklopedia of Journal, 2025)
Blood glucose levels are closely related to diabetes mellitus. Diabetes mellitus is a non-communicable disease where sufferers cannot automatically regulate glucose levels in their blood. Diabetes mellitus is also a chronic disease characterized by increased blood sugar levels (hyperglycemia). Lack of sleep can affect the function of the endocrine system, especially in impaired glucose tolerance, insulin resistance, and reduced insulin response, so that poor sleep quality can have an impact on student health and academic achievement. The aim of this research was to determine blood glucose levels in final year students of the D-III Health Analyst study program at Abdurrab University. The method used in this research is Point Of Care Testing (POCT) which uses capillary blood samples. The research results showed that 24 respondents had normal blood glucose levels, and 6 respondents had abnormal blood glucose levels. It can be concluded that respondents who have abnormal levels are because they often consume energy drinks  when  staying  up  late,  while  normal  respondents  do  not consume energy drinks.Keywords: Temporary Blood Glucose, Diabetes, Students